El regalo de los quince años: una historia de pasiones, intereses, ideologías y luchas - Pignata, Noris (Cuadernos de Trabajo Social, 2007)
The Gift for a Fifteenth Birthday1: A Story about Passions, Special Interests, Ideologies and Struggles. Since the recovery of democracy in Argentina, the legal situation of minors has been taken into account by juridical agents. The 80’s was a period of discovery of the most flagrant violations of the human rights of children, when legal rules began to be applied that consider them objects of State actions. To incorporate into the scenario the dialogue of the human being, to put forth rights and obligations of the State, leaving behind talk of charity. The inclusion of the Convention on the Rights of Children, its reception in the National Constitution, controversies about the defense of State guardianship and building of the integral protection of rights. The 90’s, with different actors and situations influencing proposed legal modifications. The new century and the hope of achieving legal change as a consequence of new strategies of collective efforts and the conviction of politicians of the need for reform. The new legislation shows us the relationship between the State and children with a focus on respect for family life. A different role for social organizations that work with children, considering how they see and hear the new citizen. Practices conspiring against the effectiveness of the law, the gap between talk and action shows us the long distance that still needs to be covered.
Keywords: Children’s rights; Legislation; State’s patronage; Convention; Civil society; Family; Subjects of rights; Integral protection; Public policies; Right to be heard